Penerapan Model PBL Untuk Meningkatkan Hasil Belajar Pak pada Siswa Fase D SMP Negeri 4 Botomuzoi Kecamatan Botomuzoi Kabupaten Nias Sumatera Utara - Elisama Laia (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This Classroom Action Research (CAR) aims to enhance the learning outcomes of Catholic Religious Education (CRE) for seventh-grade students in Phase D at SMP Negeri 4 Botomuzoi, Nias Regency, through the implementation of the Problem-Based Learning (PBL) model. The research is motivated by the desire to improve the quality of CRE instruction and student learning outcomes, particularly on the topic